Theory and analysis of nonlinear neutral pantograph equations via Hilfer fractional derivative (Nonlinear Studies, 2017)
In this paper, we study the theory  and analysis of nonlinear neutral  pantograph equations with Hilfer fractional derivative using Schauder fixed point theorem. In addition, we discuss Ulam stability of the system by employing Banach contraction principle.